Four Years in, What Are the Research Priorities for Long COVID? A Research Priority‐Setting Partnership Between People With Lived Experience, Carers, Clinicians and Researchers - Aileen Grant; Emma Stage; David Blane; Helen Goss; Jane Ormerod; Stuart McIver; Edward Duncan; Gail Patel; Abi Campbell; Paul Manson; Ganesh Subramanian; Kay Cooper (Wiley, 2024)
ABSTRACT Introduction Long COVID is a life‐limiting condition that affects 65 million people worldwide. It devastates lives with uncertain illness trajectories, and yet, there are many research uncertainties as there is a lack of understanding of its causes, effective treatments and management plans. We set out to identify current research priorities for people with Long COVID, carers, healthcare professionals and researchers. Methods A systematic literature review and previous Long COVID priority‐setting exercises identified three broad under‐researched areas of Long COVID research within the fields of Public Health and Health Services Research: symptoms; managing day‐to‐day life; and the emotional impact of Long COVID. We disseminated an elicitation survey that asked for research questions in these areas; responses were analysed and summarised into 42 research questions. A survey was then disseminated, asking respondents to prioritise these 42 questions. Workshops were held with people with Long COVID, carers, healthcare professionals and researchers to analyse responses and agree the top 10 priorities. Results The top priorities in order were pharmacological treatment of Long COVID; understanding the pathophysiology; nonpharmacological symptom management; improving public and professional understanding of Long COVID; understanding of the long‐term risks of Long COVID; improving financial and social supports; improving understanding of postviral syndromes; diagnostics; service redesign/pathways; and the well‐being of children with Long COVID. Conclusion Four years into the pandemic, there is an emphasis on the need for research on treatment, understanding and support for people living with Long COVID. Patient and Public Contribution People with Long COVID and carers were involved in the study design, survey design, dissemination, data analysis, interpretation and reviewing and editing the manuscript.